Diversity Analysis and Physico-Morphlogical Characteritics of Indigenous Germplasm of Lablab Bean - KC, Ram Bahadur; Joshi, Bal Krishna; Dahal, Surya Prasad (Journal of Nepal Agricultural Research Council, 2016)
Germplasm characterization is an important component of crop breeding program. In characterizing indigenous beans lablab which is used for vegetables as well pulses in Nepal. Twenty three lablab beans germplasm were evaluated for different qualitative and quantitive physico-morphological charecteristics for two years during 2011 and 2012 at Horticulture Research Station, Malepatan, Pokhara. The germplasm showed considerable variations in most of the qualitative and quantitative traits. Leaf size, vine color, flower color, pod color, pod shape, pod type and seed color varied among the genotypes. Variation was also observed in yield attributing characters eg, pod length and width, 10 fresh pod weight, seeds per pod and 100-seed weight. Days to 50% flowering ranged from 81 to 130 days indicating the presence of early varieties. Fresh pod weight of 10 pods was ranged from 45.0 g to 162.5 g. Multivariate analysis indicated four groups in these genotypes, among with ML-02 and ML-10 were distinct in comparioson with other genotypes. Simple selection may be considered to develop high yielding, early type varieties from these gentopypes.